The Deconstruction of Literary Criticism Approaches to the Qur’an: Amin al-Khuli’s Perspective - Moh. Mofid; Mohammad Zainal Hamdy (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2021)
The Qur'an is a collection of texts that require a very deep understanding and interpretation. Without interpretation, the text of the Qur'an remains a text that cannot speak. Literature is the result of human creation using the medium of written and spoken language, is imaginative, delivered in a unique way, and contains messages that are relatively. The purpose of this study is to explain the literary criticism approach to the Qur'an according to Amin Al-Khuli's view, so that we as Muslims understand more deeply about the contents of the Qur'an. Literary Approach as a Knife of Analysis in Understanding the Text of the Qur'an, Literary approach in interpretation actually emerged due to the large number of non-Arabs who converted to Islam and due to the weakness of the Arabs themselves in the field of literature, so it was felt necessary to explain to them about privileges and circumstances of the meaning of the content of the Qur'an. Then in the modern era the literary approach in the Qur'an was driven by Amin al-Khuli (died. 1968 AD) at the end of the twentieth century (20). He is a professor of Qur'anic studies at Cairo University. According to Amin al-Khuli, the Qur'an is the greatest book in Arabic. One of his theses states that the Qur'an is the greatest work of Arabic literature. The Qur'an has made the Arabic language never die, and along with its status as the language that God has chosen to convey His divine messages, makes the Qur'an itself as something that does not know dry.